Lipid-lowering therapy is not intensified beyond 3-months if coronary angiography with fractional flow reserve (FFR) suggests non-obstructive coronary disease: a missed opportunity for prevention?. (14th October 2021) - Vasudevan, R S; Xu, I; You, H; Xu, R; Taub, P R; Wilkinson, M J
Abstract: Background/Introduction: Patients with non-obstructive CAD are at risk for future ASCVD events. Coronary angiography with FFR distinguishes obstructive from non-obstructive CAD, however, it is unknown how FFR assessment impacts subsequent lipid management in obstructive vs non-obstructive CAD. Purpose: Examine patterns in intensification of lipid-lowering therapy after FFR assessment in those with obstructive vs non-obstructive CAD. Methods: Records were reviewed from patients at a single institution who underwent FFR, instantaneous wave free ratio (iFR), or computed tomographic (CT)-FFR assessment between 2013–2020. Obstructive CAD was defined as presence of ≥1 lesion with FFR ≤0.8, iFR ≤0.89, or CT-FFR ≤0.8, or presence of obstructive CAD by visual assessment. The impact of obstructive vs non-obstructive CAD on the management of atherogenic lipids (LDL-C and non-HDL-C) after FFR was examined at 3, 6, and 12 months using Mann-Whitney U test. Results: 461 patients had obstructive CAD vs 338 with non-obstructive CAD. Most FFR, iFR, or CT-FFR assessments were performed for a non-ACS indication (n=628 (79%)). Mean (±SD) age was 66±11 yrs, with 248 (31%) women, and 658 (82%) white. Baseline LDL-C was similar in both groups: 2.2±1.1 mmol/L (obstructive CAD) and 2.1±0.9 mmol/L (non-obstructive CAD). Both groups had high baseline statin use (n=349 (76%) (obstructive CAD) vs n=241 (71%) (non-obstructive CAD)). At 3 months, mean LDL-C and non-HDL-C decreased in both those with obstructive (LDL-C −0.4 mmol/L, non-HDL-C −0.4 mmol/L) and non-obstructive CAD (LDL-C −0.3 mmol/L, non-HDL-C −0.4 mmol/L) (p>0.05), with a similar number of new statins initiated in each group. However, at 6 months, LDL-C and non-HDL-C increased in those with non-obstructive CAD (LDL-C +0.2 mmol/L, non-HDL-C +0.4 mmol/L), while atherogenic lipids further decreased in those with obstructive CAD (LDL-C −0.1 mmol/L (p=0.011), non-HDL-C −0.1 mmol/L (p=0.048)). Compared to non-obstructive CAD, there were more statins initiated by 6 months in those with obstructive CAD, although not statistically significant. At 12 months, LDL-C remained significantly lower in those with obstructive CAD compared to those with non-obstructive CAD (Figure, Table). Conclusions: FFR assessment appears to prompt short-term intensification of lipid-lowering therapy in both those with obstructive and non-obstructive CAD (i.e. over 3 months), but this favorable effect on atherogenic lipids is lost in those with non-obstructive CAD by 6 and 12 months. Those with non-obstructive CAD are likely to benefit from long-term intensification of atherogenic lipid-lowering therapy to prevent ASCVD events, and therefore efforts should be made to maintain intensification of lipid-lowering therapy beyond 3 months in all patients undergoing FFR assessment. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Amgen Investigator Initiated Study